2023
DOI: 10.3390/ijerph20043447
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Benefit of Real-Time Multiplex PCR Testing of SARS-CoV-2 in German Hospitals

Abstract: Background: The current Omicron COVID-19 pandemic has significant morbidity worldwide. Objective: Assess the cost–benefit relation of implementing PCR point-of-care (POCT) COVID-19 testing in the emergency rooms (ERs) of German hospitals and in the case of inpatient admission due to other acute illnesses. Methods: A deterministic decision-analytic model simulated the incremental costs of using the Savanna® Multiplex RT-PCR test compared to using clinical judgement alone to confirm or exclude COVID-19 in adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In low-resource countries, rapid antigen tests have shown to be a cost-effective strategy which has increased timely access to diagnosis, regardless of epidemic phase [ 219 , 220 , 221 ]. On the other hand, rapid molecular and multiplex tests, which in general are more expensive than RT-qPCR, show promising cost-effectiveness in studies undertaken in emergency rooms and hospital settings in high-resource countries [ 70 , 71 ]. Whatever the option, accurate diagnosis remains critical as effective treatments for COVID-19 have the potential to offer value for money to healthcare systems, people, and society [ 222 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In low-resource countries, rapid antigen tests have shown to be a cost-effective strategy which has increased timely access to diagnosis, regardless of epidemic phase [ 219 , 220 , 221 ]. On the other hand, rapid molecular and multiplex tests, which in general are more expensive than RT-qPCR, show promising cost-effectiveness in studies undertaken in emergency rooms and hospital settings in high-resource countries [ 70 , 71 ]. Whatever the option, accurate diagnosis remains critical as effective treatments for COVID-19 have the potential to offer value for money to healthcare systems, people, and society [ 222 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted during the emergency phase of the COVID-19 pandemic in hospital settings revealed that systematic screening using RT-qPCR tests of patients with respiratory symptoms can be an effective but highly resource-intensive containment strategy, unlikely to be sustained in the long run [ 69 ]. Nevertheless, as new rapid molecular testing technologies have become available, studies from high-resource countries, such as Germany, have shown promising results on the cost-effectiveness of such methods in emergency rooms and hospital settings [ 70 , 71 ]. Similarly, studies in Germany and Italy have also found economic benefits when using rapid antigen tests [ 72 , 73 ].…”
Section: The Role and Value Of Rapid Testing For The Management And T...mentioning
confidence: 99%
“…In this context, diagnostic tests are more likely to be cost-effective if they can provide accurate results quickly [220]. While clinical evidence on the cost-effectiveness of POC testing for COVID-19 is limited and immature [220], even studies using high-cost methods, such as rapid molecular tests, show considerable cost-saving benefits down the line [208,209]. For example, a study found that the use of rapid COVID-19 molecular testing in an emergency department and shock room led to a reduction of USD 285.23 in direct costs in admissions with subsequent surgery, and USD 79.02 without surgery [208].…”
Section: What Is Poc Rapid Testing?mentioning
confidence: 99%
“…This is particularly important as new rapid molecular testing technologies become available. While rapid molecular testing is in general more expensive than RT-qPCR, studies from high-resource countries have shown promising results on the cost-effectiveness of such methods in emergency rooms and hospital settings [208,209].…”
mentioning
confidence: 99%